2020
DOI: 10.1007/s00296-020-04734-x
|View full text |Cite
|
Sign up to set email alerts
|

Trends in psoriatic arthritis epidemiology in Poland

Abstract: Psoriatic arthritis (PsA) is a heterogeneous inflammatory arthritis, usually seronegative and associated with psoriasis (Ps). The prevalence and incidence of psoriatic arthritis show strong ethnic and geographic variations. The aim of the study was to assess the epidemiological trends in psoriatic arthritis in Poland. The National Health Fund (NHF) database for the period 2008–2018 was analyzed. PsA was defined as ICD-10 codes L40.5, M07, M07.0, M07.1, M07.2 and M07.3, while psoriasis as ICD-10 codes L40 and L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
(32 reference statements)
1
2
0
Order By: Relevance
“…This may imply a pressing concern of potential underdiagnosis and underscores the imperative for early detection in clinical practice. Tłustochowicz et al described in recent years a gradual rise in psoriatic arthritis detection, which confirms our observations [34].…”
Section: Discussionsupporting
confidence: 93%
“…This may imply a pressing concern of potential underdiagnosis and underscores the imperative for early detection in clinical practice. Tłustochowicz et al described in recent years a gradual rise in psoriatic arthritis detection, which confirms our observations [34].…”
Section: Discussionsupporting
confidence: 93%
“…Our study revealed an unsettling phenomenon of a considerable number of articular complaints (almost half of the study group) among polish psoriatic patients. The investigation of the National Health Fund (NHF) of psoriatic arthritis (PsA) epidemiology in Poland pinpointed increasing prevalence of the disorder in the recent decade (nowadays 73.11 cases per 100,000) [ 22 , 23 ]. Alinaghi’s et al meta-analysis showed that those data are relatable to populations of European ancestry suffering from psoriasis (PsA prevalence equal to 22.7%) [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The present study is also limited by lack of a comparator cohort for other biologics, which makes it difficult to benchmark measures of effectiveness and safety. It should be noted that there is a steady increase in the recorded prevalence of PsA in Poland [ 44 , 45 ], while the current treatment armamentarium remains limited. More data are necessary to support the decisions of providers and policy makers to enable reimbursement of novel and effective therapies.…”
Section: Discussionmentioning
confidence: 99%